Wydatki na oświatę gmin województwa świętokrzyskiego w świetle wybranych cech - Bury, Piotr; Stachowicz, Jacek (Municipal Expenditures on Education in the Świętokrzyskie Voivodship in the Light of Some Local Features, 2006)
Education counts among the most important tasks of local government in Poland. In 2003 it consumed as much as 35 per cent of its budgets. Most of money is used by two first tiers of local government: gminas and powiats (plus more than sixty biggest cities being hybrids of these two types). Due to the compulsory education in two first types of schools (age 7 to 16) it is gminas who are responsible for the majority of tasks. In Świętokrzyskie they cover as much as 62 per cent of schools and 65 per cent of the pupils. Correlation analysis revealed quite weak negative connection between the relative running costs and the size of schools, measured by number of pupils. Surprisingly, there was no correlation between the running costs and the relative wealth of local governments. Expenditures on driving pupils to schools showed expected but not strong negative correlation with the population density.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 507-516